STIMULASI MOTORIK HALUS PADA AREA SENSORIAL KELOMPOK A DI RAUDLATUL ATHFAL SYIHABUDDIN - Sania Lailatul Maulidiyah; Ika Anggraheni; Mutiara Sari Dewi (UNISMA, 2022)
This study aims to describe learning planning, learning implementation activities and assessment assessments to stimulate fine motor physics in sensory area of children in RA Syihabuddin, Klandungan Village, Dau District, Malang Regency. This study uses a qualitative research approach with the type of case study research. The method or technique of data collection in this study used the method of observation, interviews and documentation with the credibility triangulation test. The results of the research that have been done are: 1) RA Syihabuddin uses the Montessori curriculum in daily learning and there are five areas to develop children's abilities, namely the areas of mathematics, language, practical life, sensory and culture. 2) The implementation of the learning is based on the RPPH document that has been prepared before the learning begins. In classroom learning activities, children are free to choose the activities they like. Materials or teaching aids in the sensory area that are used in RA Syihabuddin to stimulate children's fine motor skills include: cylinder with knobs, pink tower, brown stairs and number bars. 3) The results of observation of the evaluation documents of group A in RA Syihabuddin showed that children's fine motor skills could be well developed with stimulation in the sensory area.